Antibody responses to lipid A, core, and O sugars of the Pseudomonas aeruginosa lipopolysaccharide in chronically infected cystic fibrosis patients. - Kronborg, G (1992)
Enzyme-linked immunosorbent assays were developed separately for the three main parts of the Pseudomonas aeruginosa lipopolysaccharide (LPS) molecule, namely, lipid A, core, and O polysaccharide. Anti-lipid A, anticore, and anti-O polysaccharide antibodies were measured in serum samples from 12 patients with cystic fibrosis (CF) in a longitudinal study covering the period before P. aeruginosa infection was established through at least 5 years of chronic infection. The serum antibody response to all parts of the P. aeruginosa LPS molecule increased during the course of chronic infection. The increase in anti-lipid A antibodies was specific for P. aeruginosa lipid A, since no increase in anti-Escherichia coli lipid A antibodies was seen. Immunoglobulin G, A, and M (IgG, IgA and IgM) antibodies were all involved in the specific systemic response to P. aeruginosa lipid A, core, and the O polysaccharides. IgG and IgA levels in particular increased during the course of infection and were significantly higher than the antibody increase seen with age in a healthy control group. The local immune response in the lungs was investigated by measuring IgG, IgA, and IgM antibodies to the separate parts of the P. aeruginosa LPS molecule in sputum samples from 18 CF patients with at least a 5-year history of chronic P. aeruginosa infection. Antibodies detected in sputum were mainly anti-lipid A and anti-O polysaccharide antibodies of the IgG and IgA isotypes. Very high IgA anti-lipid A titers were detected in sputum samples from some CF patients.